\(\left\{{}\begin{matrix}\dfrac{4ac-b^2}{4a}=1\\4a+2b+c=0\\4a-2b+c=-8\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}4ac-b^2=4a\\4a+2b+c=0\\4b=8\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}b=2\\4ac-4=4a\\4a+4+c=0\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}b=2\\ac-1=a\\c=-4a-4\end{matrix}\right.\)
\(\Rightarrow a\left(-4a-4\right)-1=a\)
\(\Rightarrow4a^2+5a+1=0\) \(\Rightarrow\left[{}\begin{matrix}a=-1\Rightarrow c=0\\a=-\dfrac{1}{4}\Rightarrow c=-3\end{matrix}\right.\)
Vậy có 2 pt (P): \(\left[{}\begin{matrix}y=-x^2+2x\\y=-\dfrac{1}{4}x^2+2x-3\end{matrix}\right.\)